2012
DOI: 10.1080/13563475.2012.673739
|View full text |Cite
|
Sign up to set email alerts
|

Coming to Terms with Power Lines

Abstract: Though infrastructure planning and provision often unsettle homeowners and communities, facilitating research has been sporadic. Via a qualitative design, this article studies homeowners' perceptions of high-voltage overhead transmission lines (HVOTLs) with respect of design, cost differentials, health effects, safety issues, visual and noise impacts, environmental damage and interference with property rights. The results support inductive modelling which situates and theorizes the risk associated with power l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Their study showed that the social benefits of burying high voltage power lines would exceed the costs in some parts of the country, such as the mountains, where the willingness of population to pay, per kilometer of power line eliminated, is higher. Elliott and Wadley (2012), who studied homeowners' perceptions of high-voltage overhead transmission lines, also identified pylon design, health effects, and visual and noise impacts as being among the major concerns [62].…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed that the social benefits of burying high voltage power lines would exceed the costs in some parts of the country, such as the mountains, where the willingness of population to pay, per kilometer of power line eliminated, is higher. Elliott and Wadley (2012), who studied homeowners' perceptions of high-voltage overhead transmission lines, also identified pylon design, health effects, and visual and noise impacts as being among the major concerns [62].…”
Section: Discussionmentioning
confidence: 99%
“…Residents' concerns about economic loss of each individual and decreased value of regional area could also give the negative effect to residents' perception (F2: [26,30,45]). Secondly, location-based concerns, due to a wider range of NGP projects, could increase the negative perception of residents (F3: [28,29,45]). Associated with this factor, poor project implementation at planning and design stage without considering surrounding environment could cause another concern (F4: [5,34]).…”
Section: Correlation Analysismentioning
confidence: 99%
“…(explosion and environmental damage) could also increase the negative perception of the resident, as a cause of conflict (F7: [22,29,45]). Though these seven conflict factors are assumed as endogenous, these factors could be correlated to each other, implying that the level of conflict is not independently affected by the seven endogenous factors.…”
Section: Analytical Framework and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the burdens coming with overhead transmission lines is presented in [3], where the authors take in consideration technical aspects (transmission loss and infrastructure costs), impact on the population (noise, electromagnetic fields and interruption of supply) and environmental effects (visual intrusion, ecosystems and land use). Population perception is a key-word in planning new energy assets [4], but the matter is so sensitive that other concepts, such as trust [5] and political ideology [6], can be drivers of success or failure stories.…”
Section: Introductionmentioning
confidence: 99%